2018
DOI: 10.3390/su10072527
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Entrepreneurial Resilience on the Success of Small and Medium Enterprises in South Africa

Abstract: Small and medium enterprises (SMEs) have a significant role to play in a country's sustainable development. The measures of a country's sustainable development include economic and social factors. The sustainability of small and medium enterprises is vital to job creation, poverty reduction, and sustainable economic growth. The high failure rate of SMEs negatively impacts on South Africa's sustainable development. The purpose of the study was to investigate the relationship between entrepreneurial resilience a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 36 publications
10
97
0
11
Order By: Relevance
“…Therefore, a strong relationship exists between resilience and entrepreneurial readiness, and thus, the null hypothesis is rejected. This study parallels statements from Mohamad [21], and Ab Wahid [55], as these authors also mentioned that a correlation exists between entrepreneurial readiness and student resilience; Fatoki's [58] study of small and medium-sized entrepreneurs in Africa revealed the same results. Subsequently, the relationship between these two variables impacts both the students and entrepreneurs.…”
Section: Does a Significant Relationship Exist Between Secondary Schosupporting
confidence: 86%
“…Therefore, a strong relationship exists between resilience and entrepreneurial readiness, and thus, the null hypothesis is rejected. This study parallels statements from Mohamad [21], and Ab Wahid [55], as these authors also mentioned that a correlation exists between entrepreneurial readiness and student resilience; Fatoki's [58] study of small and medium-sized entrepreneurs in Africa revealed the same results. Subsequently, the relationship between these two variables impacts both the students and entrepreneurs.…”
Section: Does a Significant Relationship Exist Between Secondary Schosupporting
confidence: 86%
“…In spite of this, the small business sector continues to play a significant role in the economy, as it accounts for approximately 91 per cent of all formal business entities. In addition, it contributes between 51 and 57 per cent to GDP, and small firms provide about 60 per cent of total employment (Fatoki, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is positively related to the innovation which is considered one of the traits of a successful entrepreneur. The results of the study of Fatoki (2018) indicated a positive relationship between the resilience of entrepreneurs and the success of their business. Zali et al (2012) reported that business profitability is positively correlated with the interconnection of the social networks of entrepreneur.…”
Section: Research Related To Individual Resiliencementioning
confidence: 96%